Training Synergies Between Medical Informatics and Health Services Research: Successes and Challenges - Shortliffe, Edward H. (American Medical Informatics Association, 2002)
Stanford's two decades of success in linking medical informatics and health services research in both training and investigational activities reflects advantageous geography and history as well as natural synergies in the two areas. Health services research and medical informatics at Stanford have long shared a quantitative, analytic orientation, along with linked administration, curriculum, and clinical activities. Both the medical informatics and the health services research curricula draw on diverse course offerings throughout the university, and both the training and research overlap in such areas as outcomes research, large database analysis, and decision analysis/decision support. The Stanford experience suggests that successful integration of programs in medical informatics and health services research requires areas of overlapping or synergistic interest and activity among the involved faculty and, hence, in time, among the students. This is enhanced by a mixture of casual and structured contact among students from both disciplines, including social interactions. The challenges to integration are how to overcome any geographic separation that may exist in a given institution; the proper management of relationships with those sub-areas of medical informatics that have less overlap with health services research; and the need to determine how best to exploit opportunities for collaboration that naturally occur.